Power Semiconductor Devices for High Power Current Source Converters-Overview of a symmetrical emitter turn-off (ETO) thyristor - Boonchiam, Paisan (Frontiers in Engineering Innovation Research, 2006)
This paper presents the development of an power semiconductor device for the high power current source converter (CSC). The CSC is very attractive in high power applications due to its lower output dv/dt, easy regeneration capability and implicit short-circuit protection. Traditionally. either a symmetrical gate turn-off (GTO) thyristor or an asymmetrical GTO in series with a diode is used as the power switch in the CSC. Since the GTO has a lower switching speed and requires a complicated gate driver. the symmetrical GTO based CSC usually has low dynamic response speed and low efficiency. To achieve high power rating. fast dynamic response speed and low harmonics, an advanced semiconductor device are needed for the CSC. Based on symmetrical GTO and power MOSFET technologies, a symmetrical emitter turn-off (ETO) thyristor is developed that shows superior switching performance, high power rating and reverse voltage blocking capability. Based on a six-switch CSC cell, the multilevel CSC has the advantages of high power rating, low harmonics. fast dynamic response and modularity. Therefore, it is very suitable for high power applications.